Skin cancers in renal transplant recipients: a description of the renal transplant cohort in Bern (Swiss Medical Weekly, 2010)
Background/aims: Skin tumours, in particular squamous-cell carcinomas (SCC), are the most common malignant conditions developing in transplant recipients. The aim of this study is to investigate the frequency and type of skin cancer in patients receiving immunosuppressive therapy after organ transplantation. Methods: Multivariate logistic regression analysis was performed on data of 243 renal transplant patients who attended the dermatology outpatient clinic for the first time after transplantation in the period January 2002–October 2005. Results: We found an increased risk of actinic keratosis (AK) and SCC in renal transplant recipients with a basal cell carcinoma (BCC) / SCC ratio of 1:7. Older patients had AK more frequently (odds ratio [OR] 1.11, 95% confidence interval [CI] 1.06–1.15; p